Shelley and the Revolution in taste : the body and the natural world - Morton, Timothy, 1968- (Cambridge studies in Romanticism., 1994)
"This book brings together the themes of diet, consumption, the body, and human relationships with the natural world, in a highly original study of Shelley. A campaigning vegetarian and proto-ecological thinker, Shelley may seem to us curiously modern, but Morton offers an illuminatingly broad context for Shelley's views in eighteenth-century social and political thought concerning the relationships between humanity and nature. The book is at once grounded in the revolutionary history of the period 1790-1820, and informed by current theoretical issues and anthropological and sociological approaches to literature. Morton provides challenging new readings of much-debated poems, plays, and novels by both Percy and Mary Shelley, as well as the first sustained interpretation of Shelley's prose on diet. With its stimulating literary-historical reassessment of questions about nature and culture, this study will provoke fresh discussion about Shelley, Romanticism, and modernity."--Pub. desc